Transformers Rescue Bots. Outdoor adventures [videorecording (DVD)] - Chew, Nathan; Altieri, Kevin (Shout! Factory Kids, 2018)
On an island off the coast of Maine, four Transformers go undercover and team up with a family of first responders.